2012
DOI: 10.1007/s11239-012-0811-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of initial warfarin response in obese patients versus non-obese patients

Abstract: Achieving therapeutic anticoagulation with warfarin is complicated by substantial inter-patient and intra-patient variability with numerous factors known to influence dose requirements. Obesity is one factor for which there remains no study to date investigating its initial effect on warfarin response assessed by INR, stratified by BMI category in hospitalized patients. To compare initial warfarin response between obese and non-obese patients by evaluating average daily dose (ADD), time required to attain ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 13 publications
0
62
0
1
Order By: Relevance
“…Rosendaal's algorithm [31]. This time period was chosen because INR control in the first 12 months of warfarin therapy has been shown to be the best predictor of subsequent INR control [32]. Thus patients were excluded from the study if they had less than 12 months of observation in CPRD after the index date.…”
Section: Dependent Variable: Time In Therapeutic Range (Ttr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Rosendaal's algorithm [31]. This time period was chosen because INR control in the first 12 months of warfarin therapy has been shown to be the best predictor of subsequent INR control [32]. Thus patients were excluded from the study if they had less than 12 months of observation in CPRD after the index date.…”
Section: Dependent Variable: Time In Therapeutic Range (Ttr)mentioning
confidence: 99%
“…Clinical variables: Body mass index (BMI), smoking history, alcohol consumption and substance abuse (non-alcohol) [17,18,32,33]. Comorbidities that are shown to worsen anticoagulation control, that are treated with medications that interact with warfarin or that are associated with chaotic lifestyle or poor adherence: acute respiratory infection, cancer, chronic liver disease, chronic kidney disease, chronic lung disease (COPD and asthma), hyperthyroidism, hypothyroidism, epilepsy, bipolar disorder, dementia, major depression, congestive heart failure, hyperlipidaemia, hypertension, diabetes, vascular disease (prior myocardial infarction, peripheral artery disease or aortic plaque), history of stroke, history of bleeding, chronic use of pain medication, osteoarthritis and rheumatoid arthritis [15][16][17][18][34][35][36][37][38][39].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…The study by Wallace et al [15], including 211 patients with various body weights, determined the percentage of patients achieving international normalized ratio (INR) values within the therapeutic range before being discharged from hospital: the obtained ratios were 71.1% of patients with normal body weight as compared to 42.3% of patients with obesity and 38% of patients with morbid obesity. Compared to patients with normal body weight, obese patients, and particularly morbidly obese patients, required more time to achieve therapeutic INR values (6 days vs. 8 and 10 days, respectively).…”
Section: Vitamin K Antagonistsmentioning
confidence: 99%
“…For example, Wallace et al (24) investigated the association between BMI and the first TTA time according to the foreign BMI classification criteria. The results of this study demonstrated that ~50% of patients with low/normal weight or overweight achieved the required standards within day 6 of treatment (P<0.0001); whereas 50% of obese and morbidly obese patients achieved the standards on days 8 and 10 of treatment, respectively.…”
Section: Initial Dosage (Mg) Heart Failure Liver Function -----------mentioning
confidence: 99%
“…The daily average dose of warfarin was also increased in obese patients, as compared with the patients without obesity (P<0.05). Therefore, Wallace et al (24) concluded that BMI was associated with the patient's sensitivity to warfarin, and could influence the warfarin dose and initial TTA time. Another previous study suggested that the reduced sensitivity of obese patients towards warfarin was due to the increased drug distribution volume in obese patients (25).…”
Section: Initial Dosage (Mg) Heart Failure Liver Function -----------mentioning
confidence: 99%